Getting gender issues into people’s heads and hearts - Puskur, Ranjitha (International Livestock Research Institute, 2011)
Expert Assessment of What’s (Still) Needed for Agricultural Development in Poor Countries. The gender-specific disadvantages and inequities faced by rural women in poor countries create challenges for the research and development specialists working to help them empower themselves. Political, social and cultural environments all need to change before most women will be able to take a larger role in generating incomes. Men and women both need to be involved for that to happen. And when that does happen, men and women both will benefit from women’s empowerment.